Pierwsza Pomorska Wystawa Rolnictwa i Przemysłu w Grudziądzu (1925 r.) w świetle lokalnych artykułów prasowych - Knyspel-Kopeć, Renata (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2017)
Pomeranian Exhibition of Agriculture and Industry held in Grudziądz held from 26 VI–12 VII 1925, it was one of the largest exhibitions of Polish interwar period. Its purpose was to show the Polish economy on the newly reclaimed lands of Pomerania. The exhibition had a total of 56 facilities, 28 of which built the Trade Committee, and 28 private exhibitors. Among the buildings was the largest pavilion of industry, stood out a marine pavilion, located in a maritime exhibition. The event was attended by about 450 exhibitors, of which 186 accounted for by agriculture, 81 at the factory industry, 100 for crafts, 37 culture and art, the rest to other departments. In addition to the issued about 1000 animals. The exhibition was a great success moral because it opened the Polish President Stanislaw Wojciechowski in the presence of three ministers, and was visited by many visitors from home and abroad. In addition an important task to present the economic achievements of the Polish state, the first Pomeranian exhibition was still aims political-national. During the growing German revisionism threatening the integrity of the western border of the Republic, it was manifested Polishness Pomerania and highlighted achievements of the district in terms of economic and cultural development. Probably in the country hoped to soften the hostile German propaganda.